Plantback Restrictions for Herbicides Used in South Florida Sugarcane - Curtis Rainbolt (EDIS)
SS-AGR-273, a 3-page fact sheet by C. Rainbolt, condenses rotational crop restrictions for herbicides registered for use in Florida sugarcane into one table for use in planning weed control programs. Published by the UF Department of Agronomy, July 2007.